Re: Effect of ADAM28 on carcinoma cell metastasis by cleavage of von willebrand factor - Alonso, Daniel Fernando (2012)
I read with great interest the elegant work by Mochizuki et al. ( 1 ) providing novel experimental evidence for the crucial role of von Willebrand factor (VWF), a prominent plasma protein associated with blood coagulation, in resistance to metastasis. The authors found that aggressive human breast and non-small cell lung carcinoma cells expressing high levels of ADAM28 are able to avoid VWF-induced apoptosis at metastatic sites. ADAM28 binds and cleaves VWF, thus enhancing metastasis by favoring cancer cell survival within the blood vessels. I completely agree with the authors in the sense that ADAM28 can be a potential molecular target for cancer therapy, and the development of selective inhibitors of the proteinase is expected. However, another strategy could be to raise the levels of VWF by a pharmacological intervention to stimulate a natural defense against metastasis formation.